Effect of hydrostatic pressure on water and solute transport in post-tensioned grout - Rutambara Sonawane (Discover Civil Engineering)
Abstract Post-tensioned (PT) structures face critical durability challenges related to grout deficiencies, particularly concerning water segregation and solute transport at elevated heights. This study investigates the effects of hydrostatic pressure on water and solute transport in PT grout systems using modified Schupack pressure tests. Three grout types (two commercial PT grouts and one neat cement grout) were evaluated under varying conditions: constant pressure (50 PSI) with different water contents, and varying pressures (10–100 PSI) with fixed water content. Results demonstrate that hydrostatic pressure significantly influences water separation, with bleed volumes increasing proportionally to pressure across all grout types. Commercial grouts maintained relatively low bleed volumes (≤1.5%) compared to neat grout (>25%) at higher pressures. At maximum pressure of 100 PSI, neat grout exhibited bleeding rates of 27.8%, while Grout A and B maintained stability with maximum bleeding of 1.4% and 1.2% respectively. Notably, sulfate transport exhibited a complex relationship with pressure, peaking at approximately 50 PSI (equivalent to ~120 ft elevation) before declining at higher pressures. For grouts with 30% additional water, sulfate concentrations peaked at 50 PSI (2800 ppm for Grout A) before declining to 1950 ppm at 100 PSI. These findings suggest implementing staged grouting procedures with intermediate anchorages every 100 ft for structures exceeding 120 ft in height, while maintaining strict water content control within ±2% of manufacturer specifications. The results provide practical guidance for PT construction, particularly for structures with significant vertical deviations, and highlight the need for specialized consideration in applications exceeding 120 ft in height.